Air pollution, noise exposure, and metabolic syndrome – A cohort study in elderly Mexican-Americans in Sacramento area. (January 2020) - Yu, Yu; Paul, Kimberly; Arah, Onyebuchi A.; Mayeda, Elizabeth Rose; Wu, Jun; Lee, Eunice; Shih, I-Fan; Su, Jason; Jerrett, Michael; Haan, Mary; Ritz, Beate
Highlights: Metabolic syndrome is prodromal to many diseases of aging. Prevalence of metabolic syndrome is increasing especially among Mexican-Americans. Few longitudinal cohort studies focus on environment & health in Mexican-Americans. Few studies in North America have assessed health impacts of noise exposures. Traffic-related NOx and noise are linked with metabolic syndrome or its components. Abstract: Background: Previous studies suggested that air pollutants may increase the incidence of metabolic syndrome, but the potential impact from traffic sources is not well-understood. This study aimed to investigate associations between traffic-related nitrogen oxides (NOx) or noise pollution and risk of incident metabolic syndrome and its components in an elderly Mexican-American population. Methods: A total of 1, 554 Mexican-American participants of the Sacramento Area Latino Study on Aging (SALSA) cohort were followed from 1998 to 2007. We used anthropometric measures and biomarkers to define metabolic syndrome according to the recommendations of the Third Adult Treatment Panel of the National Cholesterol Education Program (NCEP ATP III). Based on participants' residential addresses at baseline, estimates of local traffic-related NOx were generated using the California Line Source Dispersion Model version 4 (CALINE4), and of noise employing the SoundPLAN software package. We used Cox regression models with calendar time as the underlying time scale to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for associations of air pollution or noise with metabolic syndrome or its components. Results: Each per unit increase of traffic-related NOx (2.29 parts per billion (ppb)) was associated with a 15% (HR = 1.15, 95% CI: 1.04–1.28) lower level of high-density lipoprotein cholesterol (HDL-cholesterol), and each 11.6 decibels (dB) increase in noise increased the risk of developing metabolic syndrome by 17% (HR = 1.17, 95% CI: 1.01–1.35). Conclusion: Policies aiming to reduce traffic-related air pollution and noise might mitigate the risk of metabolic syndrome and its components in vulnerable populations.